ANALISIS TENTANG KOMPETENSI DAN KINERJA PETANI PEMBUDIDAYA IKAN KOLAM APUNG (UKM) DI KABUPATEN BANDUNG BARAT - dede R Oktini (Universitas Islam Bandung, 2017)
The government of west java seeks to increase production of freshwater fish to persue food self sufficiency. The needs of the community are very high. Fresh fish and sea fish have enormous potential but fish production has not been able to meet the demand. This research conducted of farmers of fresh water fish in Bandung Barat district. The weakness of the fishery sector particularly at Bandung Barat district mainly lies in the aspect of competence of human resources concerned commitment, managerial competence (financial competence, human resource competence, quality management competence, readiness of raw materials management, strategic management competencies), technical ability (mastery of technical aspects of production, mastery of technical aspects of product design, marketing management). This weakness impact on the low performance of farmers. Inefficient production results in low productivity. Directional coaching is required and continuous from the government and order parties in order to improve the performance of farmers so it can meet the demand of fish especially in western java.